Investing in frontier markets opportunity, risk and role in an investment portfolio - Graham, Gavin (John Wiley & Sons Canada, Ltd., 2013)
The only comprehensive guide to reaping big returns investing in the hottest new growth markets This book makes a compelling case that, just as today's well-rounded portfolio includes emerging market funds, tomorrow's well-rounded portfolio will include frontier market funds. More importantly, it alerts you to the vast opportunities and potential pitfalls of investing in frontier markets while providing expert advice and guidance on how to research and invest in the most promising frontier growth markets. Widely considered to be the next emerging markets, frontier markets, such as those of cer.